The Impact Of Brand Endorser And Perceived Value On Purchase Intention On Local Brand Emina - Tristiani, Josephine Nikita; Apriyana, Nurliya (SEAN Institute, 2024)
This study examines the influence of brand endorsers, specifically their attractiveness, expertise, and trustworthiness, as well as perceived value on the purchase intention of local cosmetic brand Emina. Using a quantitative approach, data were collected from 151 respondents in Jabodetabek, consisting primarily of women (83.4%), aged 19-24 years (62.3%). The results indicate that attractiveness significantly influences purchase intention (p=0.005, t=2.778), with a positive coefficient of 0.297, while trustworthiness (p=0.583, t=0.549) and expertise (p=0.264, t=1.116) show no significant impact. Perceived value also significantly affects purchase intention (p<0.001, t=3.881) with a coefficient of 0.308. These findings highlight the importance of selecting visually appealing endorsers who align with the brand's youthful image and leveraging marketing strategies that emphasize product value, including functional, emotional, and social benefits. Future studies are encouraged to include credibility attributes and expand the research to broader demographic and geographic scopes to further refine these insights. Recommendations for Emina include utilizing digital platforms such as Instagram and TikTok for visually engaging campaigns and focusing on innovative product development to strengthen brand appeal among young consumers.